Drama of Avangers in Time Capsule as Practice of Politic-Cultural Representation (Cultural Appropriation or Cultural Appreciation?) - Mote, Edoardo (POLITEA, 2018)
At the inauguration of Time Capsule in Merauke, Mrs, Iriana have carried a Papuan child on her back while stepping on the place where all hopes and dream of Indonesia children kept until 2085 to be opened. She then obtained many compliment from people across the islands of Indonesia. People looked it as a form of empathy for Papuan’s problems.Actually, what Mrs. Iriana did was political communication through practice of cultural representation. Her performation on that event was then framed as a cultural appreciation for Papuan culture and also become message for Papuan that she understand and have big empathy for Papuan problem. Yet, as we see in this Paper, I problematize the claim about this frame through theory of Eating the Other from Bellhook.Eating the Other as negative model of dominative culture adopting sub-ordinate culture. By adopting element of sub-ordinate culture, the dominant can gain control to reproduce meaning of cultural codes and political representation at the politic stage. The control is by absorbing the sub-ordinate culture (assimilation)  and removal subject of culture sub-ordinate in the public area. In this case, eating the other is operationalized through cultural appropriation as an oppositional form of cultural appreciation.Cultural appropriation can be detected when someone who practice of cultural representation of other’s culture does bias of knowledge, values and socio-historical context where this culture come from. By this false practice of cultural representation, someone falls into an imaging merely without any substance. Even, it can be seen as humiliate for people who have that culture. In the other words, this is a bad practical of political representation at the politic stage and this is fatal for political communication as a whole.My conclusion in this paper is what Mrs. Iriana did at the event is felt into cultural appropriation because it was only for merely imaging in front the people. The main reason is because her practice of cultural representation did not reflect her real act for relief the suffer of Papuan Mothers who live under poverty, less healthy service, double burden and another kind of violence that is faced in everyday of their life. This argument is affirmed by what Jokowi her husband as president have bad track record of human rights issue in Papua. Keyword : Eating the Other, Practice of Cultural Representation, Cultural Appropriation, Political Representation, Mrs. Iriana,  Papuan Mothers